TUKANG OJEK DI LINGKUNGAN DUA KELURAHAN BATUKOTA KECAMATAN MALALAYANG KOTA MANADO - Bassay, Selfina (Universitas Sam Ratulangi, 2016)
Problems which has grown and developed in urban areas is one of the most problematical today. In an effort to meet certain needs life, everyone should make every effort to can earn a living decent. Motorcycle taxis is an opportunity a potential for those who not been given the chance in the field of employment formal. Urban village Batukota is one of areas who do not passed by vehicle common as mikrolet. That is very had a chance for people who failed to get work in the formal sector that in fact until now still work was ideal, for various reasons enter kinds of work in the informal sector. Transportation it is necessary to run their activities outdoors every day. For those who have no vehicles, public transportation or mikrolet a mainstay for. A chance to get jobs reliable main as toehold needs economy, as to be permanent workers and earn income of, does not always easy, considering opportunities the occasion not the same. There no escaping the fact currently, skills, the level of education and tissues is the main the demands in competition in the work. Will not few people has decided to performs any work by to support a family. Keywords: informal sector, employment, motorcycle